The zero-field approximation for weakly supported voltammetry: A critical evaluation - Dickinson, E; Compton, R (2010)
Voltammetry under weakly supported conditions can be modelled using the zero-field approximation [1], which accurately reproduces experiment for a range of systems with electrodes larger than nanoscale. We examine this approximation critically to justify its use, and consider when it may be inapplicable. A lower limit is placed on the radius of electrode for which the double layer and the diffusion layer are effectively decoupled. The success of the zero-field approximation is shown to be dependent on the site where electron transfer really takes place; only if electron transfer is infinitely fast is the approximation blind to these effects. © 2010 Elsevier B.V. All rights reserved.